Westonci.ca is the premier destination for reliable answers to your questions, provided by a community of experts. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.

Transform the equation so that both terms with variables are on the left side of the equation.

Transform The Equation So That Both Terms With Variables Are On The Left Side Of The Equation class=

Sagot :

Step-by-step explanation:

P = height of Paul.

S = height of Steve.

t = height of Theresa.

P = 1 1/2 t - 16 = 3t/2 - 16

S = 1 1/3 t - 6 = 4t/3 - 6

because Paul and Steve have the same height, we can say

P = S

3t/2 - 16 = 4t/3 - 6

3t/2 - 10 = 4t/3

9t/2 - 30 = 4t

9t - 60 = 8t

t = 60

so,

Theresa is 60" tall.

Paul and Steve are 4×60/3 - 6 = 240/3 - 6 = 80 - 6 = 74" tall